Comparative analysis of torsional and cyclic fatigue resistance of ProGlider, WaveOne Gold Glider, and TruNatomy Glider in simulated curved canal - Pedro de Souza Dias; Augusto Shoji Kato; Carlos Eduardo da Silveira Bueno; Rodrigo Ricci Vivan; Marco Antonio Hungaro Duarte; Pedro Henrique Souza Calefi; Rina Andréa Pelegrine (Restorative Dentistry & Endodontics)
ObjectivesThis study aimed to compare the torsional and cyclic fatigue resistance of ProGlider (PG), WaveOne Gold Glider (WGG), and TruNatomy Glider (TNG).Materials and MethodsA total of 15 instruments of each glide path system (n = 15) were used for each test. A custom-made device simulating an angle of 90° and a radius of 5 millimeters was used to assess cyclic fatigue resistance, with calculation of number of cycles to failure. Torsional fatigue resistance was assessed by maximum torque and angle of rotation. Fractured instruments were examined by scanning electron microscopy (SEM). Data were analyzed with Shapiro-Wilk and Kruskal-Wallis tests, and the significance level was set at 5%.ResultsThe WGG group showed greater cyclic fatigue resistance than the PG and TNG groups (p < 0.05). In the torsional fatigue test, the TNG group showed a higher angle of rotation, followed by the PG and WGG groups (p < 0.05). The TNG group was superior to the PG group in torsional resistance (p < 0.05). SEM analysis revealed ductile morphology, typical of the 2 fracture modes: cyclic fatigue and torsional fatigue.ConclusionsReciprocating WGG instruments showed greater cyclic fatigue resistance, while TNG instruments were better in torsional fatigue resistance. The significance of these findings lies in the identification of the instruments’ clinical applicability to guide the choice of the most appropriate instrument and enable the clinician to provide a more predictable glide path preparation.